Experience of using Xenical for pilots - A S Ametov; A A Belykh (Ожирение и метаболизм, 2008)
Lack of exercise, hypoxia, stress, constant psychological stress, longer shifts, a violation of the feeding process contribute to the development of metabolic disorders. Thus, persons Summer Special can be seen as a model for the study of risk factors for type 2 diabetes and the development of optimal preventive measures that determined the relevance and purpose of the study. The purpose of research - to evaluate the effectiveness of the correction of overweight and disorders of carbohydrate and lipid metabolism in patients with risk factors for type 2 diabetes. For the correction of body weight was used Orlistat (Xenical) - specific inhibitor of gastrointestinal lipases, acting locally in the lumen of the gastrointestinal trakta.Materialy and methods The study was performed at the Central Clinical Hospital of Civil Aviation. The study found that those aircrew who are overweight are at high risk of developing type 2 diabetes, which is due on the one hand, metabolic disorders due to abdominal obesity, and on the other - especially the professional activity (physical inactivity, a violation of the process food, emotional stress). As an effective therapy to persons aircrew appropriate to recommend treatment with Xenical against the background of a moderately hypocaloric diet combined with the expansion of physical activity.